PERANCANGAN MEDIA PROMOSI VIDEO YOUTUBE KOLEKSI SANGGAR GUBUG WAYANG MOJOKERTO BERBASIS BUDAYA SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Imam, Choirul; Budiardjo, Hardman; Hidayat, Wahyu (Jurnal Art Nouveau, 2017)
The purpose of design media promotion Sanggar Gubug Wayang  Mojokerto in video youtube based culture in an effort to increase brand awareness is as a source of information in order that the large public can know and preserve the culture of Indonesia. Than, this research using analysis research with descriptive-qualitative that is observation, interview, and literature study to get the data used to support the production of design media promotion Sanggar Gubug Wayang Mojokerto in video youtube. And analyzed using several stages, that is observation Extend, Improve persistence, Triangulation, negative case analysis, use of reference materials, Using check. After analysis of the data found a design concept or keyword design media promotion that is "interest". Description of "interest" is interesting. The concept of "interest" the purpose to influence adolescent and lovers of culture and art community Indonesia which has the properties Conserve (preserve) and Art (creating something of high value). This means that with the concept of "interest" is expected Sanggar Gubug Wayang more known the large public and especially adolescents can get to know and be able to preserve the culture of Indonesia.Keywords: Media promotion, Sanggar Gubug Wayang, Youtube video